1978
DOI: 10.1083/jcb.76.3.675
|View full text |Cite
|
Sign up to set email alerts
|

Rat liver nuclear skeleton and ribonucleoprotein complexes containing HnRNA.

Abstract: Rat liver nuclei deprived of chromatin and nucleoplasm show a spongelike network which preserves its connection with nucleoli, the inner membrane of the nuclear envelope, and nuclear pore complexes. It contains all of the HnRNA, provided the endogenous proteolytic activity is inhibited by a proteolytic inhibitor such as phenylmethyl sulfonyl chloride (PMSC) or the fluoride form (PMSF). In the absence of these proteolytic inhibitors, HnRNA is dissociated from the spongelike network and sediments in a sucrose gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
82
0
1

Year Published

1981
1981
1996
1996

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(92 citation statements)
references
References 28 publications
9
82
0
1
Order By: Relevance
“…Previous work has shown that hnRNAs are bound to the nuclear matrix (36)(37)(38)(39). It was possible that genes were associated with the matrix through their association with this bound hnRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that hnRNAs are bound to the nuclear matrix (36)(37)(38)(39). It was possible that genes were associated with the matrix through their association with this bound hnRNA.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the nuclear skeleton, a structure similarly isolated as the nuclear matrix, binds ribonucleoprotein (RNP) complexes which show rapid labeling of the hnRNA [37]. It has also been shown that the DNA-P fraction is enriched in RNA [20].…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear skeleton appears to support DNA replication (Pardoll et al, 1980 ;Tubo et al, 1985) and transcription (Robinson et al, 1983 ;Ciejek et al, 1983 ; by tightly anchoring DNP. This structure also binds hnRNP (Herman et al, 1978 ;Miller et al, 1978a ;Van Eekelen and Van Venrooij, 1981) and snRNP (Miller et a/., 1978b ;Gallinaro et al, 1983) Rousseau, 1985). RNA is a potent competitor for the binding of receptor-androgen (Liao et al, 1980), -oestrogen (Feldman et al, 1981 ;Chong and Lippman, 1982), and -dexamethasone (Tymoczko et al, 1982) (Palmiter and Carey, 1974 ;Cox, 1977) ; similarly, oestrogen or progesterone was demonstrated to affect the half-life of coinalbumin mRNA in chick oviduct (Mc Knight and Palmiter, 1979), and androgen to modulate the half-life of prostatic binding protein mRNAs (Page and Parker, 1982).…”
Section: Introductionmentioning
confidence: 99%